Heroism of population of Semipalatinsk during the Great Partiotic War (Journal of history, 2020)
This article is devoted to the heroism of soldiers from Semipalatinsk region during the Great Patriotic War. From the first days of the Great Pa- triotic War soldiers from Semei were called for the active military Soviet Army to fight against the German fascists in front flank and defend their Motherland. The author states also, that in the years of Great Patriotic war a great number of infantry divisions were formed, and in autumn of 1941 the 8th infantry was formulated in city of Semipalatinsk which had hero- ically fought against enemy troops. The article also tells about that in big battles in Great Patriotic war, soldiers from Semipalatinsk were appropri- ated the rank of Hero of Soviet Union for their courage, and they were awarded by the Order of Glory of the 3-d degrees and by the Order of the Red Banner. The author gives also facts that from the first days of war the party committee of Semipalatinsk city and government bodies effectively reorganized productions of different goods in accordance with the require- ments of war-time.